(untitled) (Research, Society and Development, 2021)
Food waste is of concern, as at least 1.4 billion tons of food are wasted worldwide each year. Several environmental, social and economic aspects contribute to the increase in these numbers, however half of the food waste in the world could be avoided by preventive measures. Thus, this study aimed to evaluate, through a literature review, the potential use of grape by-products, such as bagasse, in the development of functional products. For this purpose, the descriptors "grape", "low quality grape", "export grape", "grape functional food" were used, "functional food grape pomace", "grape skin functional food", "junk grape", "grape", "low quality grape", "export grape", "functional food grape", "functional food grape pomace", "grape skin functional food", "junk grape". The database used was PubMed (National Library of Medicine), Capes Journal Portal, LILACS (Latin American and Caribbean Literature in Health Sciences), Science Direct, Scorpus and Crossref, using descriptors in English and Portuguese, and selecting articles published between the years 2000 to 2022. 942 articles were found (PubMed= 546 ScienceDirect= 373; Scielo= 25), of which 80 articles were selected, and of these 68 were excluded for not meeting the inclusion criteria that they were functional products developed through the by-products of the grape that would be discarded, and having, as well as the year of publication of the study, occurred from the year 2000. And so, 15 articles were used. Most of the works applied the grape to the development of flour for the production of cakes and the enrichment of yogurts, in addition to producing cookies, jellies and cereal bars. Through the review carried out, it was possible to show that the use of a wine residue that has the potential to provide health benefits through the development of functional products, reducing the amount of these residues in industry and the environment, with the possibility also of reducing costs in the production of foods.